Animal Nullius: Review of Irus Braverman, Settling Nature: The Conservation Regime in Palestine-Israel (UMN, 2023) - Boast, Hannah (Humanimalia, 2023)
Review of:Irus Braverman. Settling Nature: The Conservation Regime in Palestine-Israel. Minneapolis: University of Minnesota Press, 2023.362 pp. 47 b&w photos.$116.00 (hb) ISBN 978-1-5179-1205-5$29.00 (pb) ISBN 978-1-5179-1526-1